Kompetensi Pedagogik Ustadz Di Pondok Pesantren Darussalam Sumbersari Kencong Kepung Kediri - Fadhil Akbar; Nailal Muna (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
The focus of this study is the pedagogical competence of the clerics in the learning of formal systems at Darussalam Sumbersari Kencong Kepung Kediri Islamic Boarding School. The focus is reduced in the form of questions, [1] Pedagogical competence of teachers in student learning, and [2]. Factors that influence internally and externally on pedagogical competence in learning. This type of research approach is qualitative phenomenology, with a case study design. Data collection is done by in-depth interview techniques, observation, and study documentation. While the data analysis technique, researchers used an interactive analysis model that contained four interrelated components, namely: data collection, data simplification, data exposure, withdrawal and submission of conclusions. The results of this study can be concluded as follows: [1]. Theoretical pedagogical competence is applied by educators in learning activities at Darussalam Sumbersari Islamic Boarding School, [2]. The application of indicators for the basics of pedagogical competence is an important factor in the clerical pedagogical competence at Darussalam Islamic Boarding School in Sumbersari Kencong, Kedung Kediri.